The Tumor Suppressor Interferon Regulatory Factor 2 Binding Protein 2 Regulates Hippo Pathway in Liver Cancer by a Feedback Loop in Mice. Issue 6 (16th February 2020) - Feng, Xue; Lu, Tiantian; Li, Jinhui; Yang, Ruizeng; Hu, Liqiao; Ye, Yi; Mao, Feifei; He, Lingli; Xu, Jinjin; Wang, Zuoyun; Liu, Yingbin; Zhang, Yonglong; et al.
Abstract : Background and Aims: The conserved Hippo pathway regulates organ size, tissue homeostasis, and tumorigenesis. Interferon regulatory factor 2 binding protein 2 (IRF2BP2) was originally identified as a transcriptional corepressor. However, the association between IRF2BP2 and the Hippo pathway remains largely unknown. In addition, the biological function and regulation mechanism of IRF2BP2 in liver cancer are poorly understood. Approach and Results: In this study, we uncovered the clinical significance of IRF2BP2 in suppressing hepatocellular carcinogenesis. We showed that IRF2BP2, a direct target repressed by the Yes‐associated protein (YAP)/TEA domain transcription factor 4 (TEAD4) transcriptional complex, inhibited YAP activity through a feedback loop. IRF2BP2 stabilized vestigial‐like family member 4 (VGLL4) and further enhanced VGLL4's inhibitory function on YAP. Moreover, liver‐specific IRF2BP2 overexpression suppressed tumor formation induced by Hippo pathway inactivation. Conclusions: These results revealed the important role of IRF2BP2 in repressing liver cancer progression and highlighted a feedback loop underlying the Hippo pathway in organ‐size control and tumorigenesis.